Influence of chronic morphine exposure on serum LH, FSH, testosterone levels, and body and testicular weights in the developing male rat - Yilmaz, B; Konar, V; Kutlu, S; Sandal, S; Canpolat, S; Gezen, MR; Kelestimur, H (Hemisphere Publ Corp, 1999)
Opiate abuse has been a matter of serious concern in male adolescents. This study investigates the effects of chronic morphine administration on serum luteinizing hormone (LH), follicle-stimulating hormone (FSH), testosterone levels, testicular histology, and body and testes weight in developing male rats. Animals were subcutaneously injected with morphine (5 mg/kg) or saline (1 mL/kg) twice daily for 30 days. Body weight determinations and injections were carried out under light ether anesthesia. At the end of the experiments, the rats were decapitated and blood samples were collected. Serum levels of LH and FSH were measured. Chronic morphine administration significantly decreased serum testosterone (p <.02) and LH (p <.01) levels, but not FSH release compared to controls. Morphine exposure reduced body weight (p <.01), but bad no significant effect on the testicular weight. When the testicular tissue was histologically examined, structural features of the seminiferous tubules and Leydig cells were similar in both saline and morphine-treated animals. The results suggest that opiates affect testosterone release through the hypothalamo-hypophyseal-gonadal axis rather than by a local testicular mechanism. Chronic morphine exposure during sexual maturation may have long-term endocrine disturbances in male rats.
Keywords: FSH; LH; male fertility; morphine; testosterone